Magnetic Nanoparticles for Efficient Delivery of Growth Factors: Stimulation of Peripheral Nerve Regeneration. Issue 7 (3rd February 2017) - Giannaccini, Martina; Calatayud, M. Pilar; Poggetti, Andrea; Corbianco, Silvia; Novelli, Michela; Paoli, Melania; Battistini, Pietro; Castagna, Maura; Dente, Luciana; Parchi, Paolo; Lisanti, Michele; Cavallini, Gabriella; et al.
Abstract : The only clinically approved alternative to autografts for treating large peripheral nerve injuries is the use of synthetic nerve guidance conduits (NGCs), which provide physical guidance to the regenerating stump and limit scar tissue infiltration at the injury site. Several lines of evidence suggest that a potential future strategy is to combine NGCs with cellular or molecular therapies to deliver growth factors that sustain the regeneration process. However, growth factors are expensive and have a very short half‐life; thus, the combination approach has not been successful. In the present paper, we proposed the immobilization of growth factors (GFs) on magnetic nanoparticles (MNPs) for the time‐ and space‐controlled release of GFs inside the NGC. We tested the particles in a rat model of a peripheral nerve lesion. Our results revealed that the injection of a cocktail of MNPs functionalized with nerve growth factor (NGF) and with vascular endothelial growth factor (VEGF) strongly accelerate the regeneration process and the recovery of motor function compared to that obtained using the free factors. Additionally, we found that injecting MNPs in the NGC is safe and does not impair the regeneration process, and the MNPs remain in the conduit for weeks. Abstract : Magnetic nanoparticles (MNPs) carrying the nerve growth factor and the vascular growth factor are localized in the center of a nerve guidance conduit sutured between two nerve stumps after nerve axotomy. MNP‐mediated delivery enhances the regeneration process and the recovery of motor function, whereas the delivery of free factors, which have a short half‐life, has no effects.